Influencia del estrés laboral en el desempeño dentro del área de negocios de la cooperativa KW de la agencia Guamaní en el año 2023 - Guadalupe Yaguachi, Myriam Patricia (2025)
This scientific article aims to determine the impact of work-related stress on the performance of workers in the business area of the KW cooperative in the Guamaní agency, in order to improve the well-being of its employees and optimise their organisational performance. The research was developed using a descriptive approach and surveys were applied to identify the level of work-related stress, the associated health symptoms and the problems that derive from this type of ailment. As results, workers experience a high level of stress that negatively affects emotional and work development, the main causes were determined to be: too much workload, tight deadlines and inadequate institutional infrastructure, these factors contribute to a deterioration in interpersonal relationships and personal satisfaction, which is reflected in a lower achievement of goals. It is concluded that the employees of the KW cooperative of the Guamaní agency have recurrent health problems, which causes anxiety and compromises professional performance in order to achieve individual and collective objectives. Finally, it is recommended to implement both personal and organizational strategies to mitigate work- related stress, as well as to improve communication within the work team, and to foster an organizational environment.